Risk factor analysis and construction of prediction models of gallbladder carcinoma in patients with gallstones - Zhu, Zhencheng; Luo, Kunlun; Zhang, Bo; Wang, Gang; Guo, Ke; Huang, Pin; Liu, Qiuhua (Frontiers in Oncology, 2023)
Background: Gallbladder carcinoma(GBC) is a biliary tract tumor with a high mortality rate. The objective of this study was to explore the risk factors of GBC in patients with gallstones, and to establish effective screening indicators. Methods: A total of 588 patients from medical centers in two different regions of China were included in this study and defined as internal test samples and external validation samples respectively. We retrospectively reviewed the differences clinicopathologic data at internal test samples to find the independent risk factors that affect the occurrence of GBC. Then we constructed three different combined predictive factors(CPF) through weighting method, integral system and nomogram respectively, and named them CPF-A, CPF-B and CPF-C sequentially. Further we evaluated these indicators through Calibration and DCA curves. The ROC curve was used to analyze its diagnostic efficiency. Finally, the diagnostic capabilities of them were validated at external validation samples. Results: At internal test samples, the results showed that Five factors, including age (RR=3.077, 95%CI: 1.731-5.496), size of gallstones (RR=13.732, 95%CI: 5.937-31.762), course of gallstones (RR=2.438, 95%CI: 1.350-4.403), CEA (RR=9.464, 95%CI: 3.394-26.392) and CA199 (RR=9.605, 95%CI: 4.512-20.446), were independent risk factors for GBC in patients with gallstones. Then we established three predictive indicators CPF-A, CPF-B and CPF-C. These models were further validated using bootstrapping with 1000 repetitions. Calibration and Decision curves analysis showed that the three models fit well. Meanwhile, multivariate analysis showed that CPF-B and CPF-C were independent risk factors for GBC in patients with gallstones. In addition, the validation results at external validation samples are essentially consistent with the internal test samples. Conclusion: Age (≤58.5 vs. >58.5 years), size of gallstones (≤1.95 vs. >1.95cm), course of gallstones (≤10 vs. >10 years), CEA (≤5 vs. >5 ng/mL) , CA199 (≤37 vs. >37 U/ml) are independent risk factors for GBC in patients with gallstones.When positive indicators were ≥2 among the five independent risk factors, or the score of Nomogram >82.64, the risk of GBC was high in gallstones patients.